Cellular and humoral immune responses and breakthrough infections after three SARS-CoV-2 mRNA vaccine doses - Almendro-Vázquez, Patricia; Chivite-Lacaba, Marta; Utrero-Rico, Alberto; González-Cuadrado, Cecilia; Laguna-Goya, Rocio; Moreno-Batanero, Miguel; Sánchez-Paz, Laura; Luczkowiak, Joanna; Labiod, Nuria; Folgueira, María Dolores; Delgado, Rafael; Paz-Artal, Estela (Frontiers in Immunology, 2022)
Background SARS-CoV-2 vaccination has proven the most effective measure to control the COVID-19 pandemic. Booster doses are being administered with limited knowledge on their need and effect on immunity. Objective To determine the duration of specific T cells, antibodies and neutralization after 2-dose vaccination, to assess the effect of a third dose on adaptive immunity and to explore correlates of protection against breakthrough infection. Methods 12-month longitudinal assessment of SARS-CoV-2-specific T cells, IgG and neutralizing antibodies triggered by 2 BNT162b2 doses followed by a third mRNA-1273 dose in a cohort of 77 healthcare workers: 17 with SARS-CoV-2 infection prior to vaccination (recovered) and 60 naïve. Results Peak levels of cellular and humoral response were achieved 2 weeks after the second dose. Antibodies declined thereafter while T cells reached a plateau 3 months after vaccination. The decline in neutralization was specially marked in naïve individuals and it was this group who benefited most from the third dose, which resulted in a 20.9-fold increase in neutralization. Overall, recovered individuals maintained higher levels of T cells, antibodies and neutralization 1 to 6 months post-vaccination than naïve. Seventeen asymptomatic or mild SARS-CoV-2 breakthrough infections were reported during follow-up, only in naïve individuals. This viral exposure boosted adaptive immunity. High peak levels of T cells and neutralizing antibodies 15 days post-vaccination associated with protection from breakthrough infections. Conclusion Booster vaccination in naïve individuals and the inclusion of viral antigens other than spike in future vaccine formulations could be useful strategies to prevent SARS-CoV-2 breakthrough infections.